2022
DOI: 10.1364/oe.456653
|View full text |Cite
|
Sign up to set email alerts
|

Stimulated Raman scattering spectroscopy with quantum-enhanced balanced detection

Abstract: Quantum-enhanced stimulated Raman scattering (QE-SRS) is a promising technique for highly sensitive molecular vibrational imaging and spectroscopy surpassing the shot noise limit. However, the previous demonstrations of QE-SRS utilized rather weak optical power which hinders from competing with the sensitivity of state-of-the-art SRS microscopy and spectroscopy using relatively high-power optical pulses. Here, we demonstrate SRS spectroscopy with quantum-enhanced balanced detection (QE-BD) scheme, which works … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…To improve the signal-to-noise ratio (SNR), the squeezed light-enhanced SRS (SQ-SRS) has been demonstrated in both SRS spectroscopy [116] and SRS microscopy [117]. In [116], SRS spectroscopy was demonstrated with quantum-enhanced balanced detection (QE-BD).…”
Section: Quantum Enhancementmentioning
confidence: 99%
See 1 more Smart Citation
“…To improve the signal-to-noise ratio (SNR), the squeezed light-enhanced SRS (SQ-SRS) has been demonstrated in both SRS spectroscopy [116] and SRS microscopy [117]. In [116], SRS spectroscopy was demonstrated with quantum-enhanced balanced detection (QE-BD).…”
Section: Quantum Enhancementmentioning
confidence: 99%
“…To improve the signal-to-noise ratio (SNR), the squeezed light-enhanced SRS (SQ-SRS) has been demonstrated in both SRS spectroscopy [116] and SRS microscopy [117]. In [116], SRS spectroscopy was demonstrated with quantum-enhanced balanced detection (QE-BD). In Figure 4, the QE-SRS spectra are measured by observing the output signal of the LIA on an oscilloscope (OSC), which is shown [116].…”
Section: Quantum Enhancementmentioning
confidence: 99%
“…We assume that spatial pattern of SQV is the same as that of fundamental mode of the OPA waveguide. Thus, we calculate the spatial profile of fundamental mode by mode-solver (Modesolverpy 25 ), and use the acquired spatial profile as the target pattern for LO 14 .…”
Section: Spatial Beam Shapingmentioning
confidence: 99%
“…To overcome shot-noise-limited sensitivity of SRS microscopy, quantum-enhanced (QE-) SRS microscopy is expected as a promising technique [12][13][14][15] . R. B. de Andrade et al demonstrated QE-SRS by using continuous light source, where continuous light was mixed with squeezed vacuum at asymmetric beamsplitter, and used as SRS Stokes light.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation